Phospholipid supplementation inhibits male and female odor discrimination in mice - Morozova, Maryana; Andrejeva, Jelizaveta; Snytnikova, Olga; Boldyreva, Lidiya; Tsentalovich, Yuri; Kozhevnikova, Elena (Frontiers in Behavioral Neuroscience, 2024)
Dietary phospholipids (PLs) are promising supplements that are commonly found as natural food ingredients and emulsifier additives. The present study aimed to evaluate the effect of major PLs found in food supplements on social behavior in mice. In this study, the effect of short-term high dietary PL content was studied in terms of social odor discrimination and social interactions with male and female intruders in male mice. We used odor discrimination and habituation tests to demonstrate that PL-fed male mice tend to lose preference toward female odor and fail to discriminate against socially significant scents. At the same time, test animals recognize non-social odors. We also found that PL affected the social behavior of the test males, who tend to behave indiscriminately toward male and female intruders during direct contact. Brain metabolomic profiling revealed no major changes in the intermediary metabolism or neurotransmitter biosynthesis. At the same time, intranasal PL application resembled the effects of dietary supplementation. These data suggest that certain PL might suppress pheromone perception in the olfactory system and affect the sense of socially important odor cues.